USM CHANCELLOR EXPRESSES APPRECIATION AND THANKS TO ALL WHO HELPED FLOOD VICTIMS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 1 January 2015 Universiti Sains Malaysia (USM) Chancellor HRH Tuanku Syed Sirajuddin Ibni AlMarhum Tuanku Syed Putra Jamalullail expressed his heartfelt appreciation and thanks to all those involved in the management of flood victims especially in floodstricken Kelantan.